Big Data in Health Care Analysis: A Survey - P, Sharmila; P, Rathiga (International Journal of Computer Sciences and Engineering, 2019)
The fields of science, engineering and technology are producing data at an exponential rate important to Exabyte(s) of data everyday life. Big data helps us to travel and re-invent many areas not limited to education, health and law. This paper surveys big data with underlining the big data analytics in healthcare analysis. Big data methodologies can be used for the healthcare data analytics which provide the better decision to accelerate the business profit and customer affection, acquire a better understanding of market behaviors and trends and to provide E-Health services using Digital imaging and communication in Medicine. This paper presents an overview of big data and Health care system benefits, Tools and challenges and review on it.